2009
DOI: 10.1161/hypertensionaha.109.134569
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Blood Pressure in 8 Mouse Intercross Populations

Abstract: The genetic basis of hypertension is well established, yet very few genes that cause common forms of hypertension are known. Quantitative trait locus (QTL) analyses in rodent models can guide the search for human hypertension genes, but the excellent genetic resources for mice have been underutilized in this regard. To address this issue, we surveyed blood pressure variation in mice from 37 inbred strains and generated 2,577 mice in eight intercross populations to perform QTL analyses of blood pressure. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Eln ϩ/Ϫ rs369822 129 homozygotes, however, have an even higher SBP of 141 mm Hg. A similarly located peak was identified in a C3HxKK intercross by Feng et al (18), but in this case the total pressure difference between homozygous genotypes was only 3 mm Hg.…”
Section: Additive and Interactive Peaks Are Identified For Systolic Bsupporting
confidence: 68%
“…Eln ϩ/Ϫ rs369822 129 homozygotes, however, have an even higher SBP of 141 mm Hg. A similarly located peak was identified in a C3HxKK intercross by Feng et al (18), but in this case the total pressure difference between homozygous genotypes was only 3 mm Hg.…”
Section: Additive and Interactive Peaks Are Identified For Systolic Bsupporting
confidence: 68%
“…For example, a phenotypic screen of 37 strains of mice22 using the VPR tail‐cuff system (same as in this study) reported a 100±2 to 133±3 mm Hg range of SBPs for those animals. Other laboratories had comparable results using the same39 or different tail‐cuff systems 40, 41, 42.…”
Section: Discussionmentioning
confidence: 60%
“…However, a systematic and comprehensive evaluation of these stress‐inducing factors and their effect on hemodynamics in mice is lacking. It is believed that the mice habituate to the tail‐cuff procedure following repeated exposure and there is a common practice to “train” mice before starting an experiment 10, 21, 22. However, there is evidence that this does not happen 23, 24.…”
Section: Introductionmentioning
confidence: 99%
“…Mice from 15 inbred strains were purchased from The Jackson Laboratory and bred at Novartis Pharmaceuticals to generate nine populations of male F 2 mice for QTL analysis. Blood pressure was measured in F2 mice at 8 wk of age [QTL results for this phenotype are published (18)] and then spot urine samples were collected at 10 wk of age and analyzed with mouse albumin standards using a Roche Hitachi 917 Clinical Chemistry Autoanalyzer. DNA isolated from each F 2 mouse was genotyped by KBiosciences (Herts, UK) as described previously (18).…”
Section: Methodsmentioning
confidence: 99%